The Development of SaveOcean: Beach and Coastal Cleanup Organizer Mobile Application - Choo, Zhen Ni; Darman, Rozanawati (Applied Information Technology And Computer Science, 2024)
Marine pollution poses a rising global challenge, exacerbated by disorganized beach cleanup efforts due to a lack of systematic platforms. This project introduces the "SaveOcean: Beach and Coastal Cleanup Organizer Mobile Application" aimed at streamlining cleanup initiatives and enhancing cleanup organization and volunteer engagement. Developed for Android platforms using Object-Oriented Analysis and Design (OOAD) methodology, a web-based approach, and tools like Android Studio and Firebase, the app serves organizers, volunteers, and administrators. The organizers are able to create a cleanup while the volunteers have the option to join for a cleanup. The administrators are responsible for approving or rejecting cleanup requests. The expected outcome is a structured platform that enhances beach and coastal cleanup activities, enables organizers to schedule cleanups, allows volunteers to join, and permits administrative approvals. The app is anticipated to lead to a healthier and more sustainable coastal environment, with increased awareness and participation in conservation efforts.